Damage Detection of Offshore Structure Tubulars using Frequency Method - Tan , Kai Xian (Universiti Teknologi PETRONAS, 2020)
Structural Health Monitoring (SHM) is defined as the process of implementing a damage detection and characterization strategy for engineering structures which mainly involves in health monitoring, operational evaluation, data feature extraction, and statistical model development. Vibration-based damage detection methods are one of the popular and promising approaches in SHM. It is based on the idea that damage will alter the dynamic properties of the structure. Example, structural response, frequencies, mode shapes, damping or modal strain energy change. In this study, Structural Analysis Computer Software (SACS) was used to model the mechanical clamp on the critical members and the natural frequency from vibration was analysed through the software.